Glutamic acid decarboxylase immunoreactivity in the mossy fiber terminals of the hippocampus of genetic absence epileptic rats - (:unkn) unknown (My University, 2011)
AIM: Genetic absence epilepsy rats from Strasbourg (GAERS) provide a model of absence epilepsy. Although excessive GABA mediation within the thalamo-cortico-thalamic circuit has been shown to play a role in absence epilepsy, neuronal networks of hippocampus have recently received attention. Glutamic acid decarboxylase (GAD) was previously shown to be increased after convulsive seizures in the mossy fiber terminals (MFTs) of hippocampus. The aim of the present study was to investigate whether the change in the level of this enzyme in convulsive seizures is also observed in rats having genetic absence epilepsy. MATERIAL AND METHODS: Hippocampal CA3 and dentate regions were processed for transmission electron microscopic evaluations. Thin sections were incubated with anti-GAD65/67 antibody. The NIH Image Analysis program was used for the quantitative analysis. RESULTS: It was observed that GAD65/67 immunoreactivity was positive in CA3 and dentate gyrus MFTs of both groups and the difference in the density of immunolabeling between the groups was not statistically significant. CONCLUSION: The present study demonstrated that GABA synthesizing enzyme, GAD, is found in MFTs of Wistar and GAERS hippocampus and this enzyme does not show an increase in these terminals in absence epilepsy, in contrast to convulsive seizures.
Keywords: Animals; Male; Rats; Disease Models, Animal; Rats, Wistar; Genetic Predisposition to Disease; Epilepsy, Absence; gamma-Aminobutyric Acid; Hippocampus; Synaptic Transmission; Neural Inhibition; Dentate Gyrus; Microscopy, Immunoelectron; Mossy Fibers, Hippocampal; Rats, Mutant Strains; CA3 Region, Hippocampal; Glutamate Decarboxylase; Presynaptic Terminals